Development of raw materials storage management system for Japan-Malaysia Technical Institute - Ahmad, Hishammudin (2013)
This study is about to develop the inventory control system for managing the raw materials issuing problems for teaching and learning purposes at Japan - Malaysia Technical Institute (JMTI), Bukit Minyak, Pulau Pinang. The objectives for this study are to identify the problem involved in the current situation for raw material storage system, develop one systematic approach by using database management system and analyze the effectiveness of developed system. Microsoft Access will be used as a platform for development of the database. The material management system is about the management functions related to the complete cycle of materials flow, from the purchase and internal control of production materials to the planning and control of work-in-progress, to the warehousing, shipping and distribution of the finished product to the customer. In this study, the material planning methods is used in re-order point system under economic order quantity for control the level of raw materials inventory at JMTI storage area. Direct observation on the site and also the interview with the person-in-charge of the store will be conducted. The comparison results between before and after the implementation of the system will be presented for future development of JMTI.